2021
DOI: 10.2147/ijgm.s328522
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of m6A-Related Genes Landscape in Skin Cutaneous Melanoma to Aid Immunotherapy and Assess Prognosis

Abstract: Background: Skin cutaneous melanoma (SKCM) is the most malignant tumor among skin cancers. Immunotherapy has shown a great role in the advantageous prognosis of SKCM. However, only a small percentage of people can benefit from immunotherapy. To date, there has been insufficient evidence to reveal the prognostic value of m6A in SKCM and its relationship with the infiltration of immune cells and the efficacy of immunotherapy. Methods: Here, we synthetically analyzed 23 m6A regulators from SKCM samples collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Furthermore, SKCM treatment has been revolutionized with the approval of immune checkpoint inhibitors, which have a significant impact on the prognosis of patients with SKCM [ 36 ]. Nevertheless, only a small percentage of SKCM patients can benefit from immunotherapy [ 37 ]. Tumor immune cell infiltration can affect the sensitivity of immunotherapy, and higher immune cell infiltration scores showed a significant immune therapeutic advantage and clinical benefit [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SKCM treatment has been revolutionized with the approval of immune checkpoint inhibitors, which have a significant impact on the prognosis of patients with SKCM [ 36 ]. Nevertheless, only a small percentage of SKCM patients can benefit from immunotherapy [ 37 ]. Tumor immune cell infiltration can affect the sensitivity of immunotherapy, and higher immune cell infiltration scores showed a significant immune therapeutic advantage and clinical benefit [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…All data analyses used R software version 4.0.2. Statistical significance was defined as a P value of 0.05 [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…circIGF2BP3 reduces PD-L1 ubiquitination and subsequent proteasomal degradation by enhancing OTUB1 mRNA stability in a PKP3-dependent manner, leading to immune evasion of CD8+ T cell-mediated killing ( 169 ). It was found that there were significant differences in overall survival and immune cells infiltration between different m6A subgroups of cutaneous melanoma ( 170 ). The m6A score was positively associated with regulatory T-cell and helper T-cell content, which may explain why a high m6A score is associated with a better prognosis ( 170 ).…”
Section: Novel Immunotherapy In Gbm and Other Cancersmentioning
confidence: 99%
“…It was found that there were significant differences in overall survival and immune cells infiltration between different m6A subgroups of cutaneous melanoma ( 170 ). The m6A score was positively associated with regulatory T-cell and helper T-cell content, which may explain why a high m6A score is associated with a better prognosis ( 170 ). Furthermore, high m6A score patients presented a stronger response to novel immunotherapies, and two immune-related samples receiving anti-PD-1 or anti-PD-L1 therapy confirmed that patients in the high m6A score group had a better response to novel immunotherapy ( 170 ).…”
Section: Novel Immunotherapy In Gbm and Other Cancersmentioning
confidence: 99%